METODE AGGREGATE COST PADA PREMI PENSIUN UNTUK KASUS MULTIPLE DECREMENT - Riska br Silitonga; Hasriati '; Tumpal Parulian Nababan (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
This article discusses the aggregate cost method which is used to determine premium pension insurance under uniform assumption for the case of multiple decrements. The calculation of the premium is obtained by determining due life annuity and yearly present value benefit recieved by members of life insurance. Due life annuity and premium payment in a year is evaluated by determining in advance the life probability using uniform assumption for the case of multiple decrements.